ERM, enterprise risk management : issues and cases - Louisot, Jean-Paul.; Ketcham, Christopher (Chichester, West Sussex, United Kingdom : Wiley, 2014)
'A wealth of international case studies illustrating current issues and emerging best practices in enterprise risk managementDespite enterprise risk management's relative newness as a recognized business discipline, the marketplace is replete with guides and references for ERM practitioners. Yet, until now, few case studies illustrating ERM in action have appeared in the literature. One reason for this is that, until recently, there were many disparate, even conflicting definitions of what, exactly ERM is and, more importantly, how organizations can use it to utmost advantage. With efforts underway, internationally, to mandate ERM and to standardize ERM standards and practices, the need has never been greater for an authoritative resource offering risk management professionals authoritative coverage of the full array of contemporary ERM issues and challenges. Written by two recognized international thought leaders in the field, ERM-Enterprise Risk Management provides that and much more. Packed with international cases studies illustrating ERM best practices applicable across all industry sectors and business models Explores contemporary issues, including quantitative and qualitative measures, as well as potential pitfalls and challenges facing today's enterprise risk managers Includes interviews with leading risk management theorists and practitioners, as well as risk managers from a variety of industries An indispensable working resource for risk management practitioners everywhere and a valuable reference for researchers, providing the latest empirical evidence and an exhaustive bibliography '--
Series from jacket
Includes bibliographical references and index.
Keywords: Risk management